Cardiac Magnetic Resonance Assessment of Interstitial Myocardial Fibrosis and Cardiomyocyte Hypertrophy in Hypertensive Mice Treated With Spironolactone. Issue 3 (25th June 2014) - Coelho‐Filho, Otavio R.; Shah, Ravi V.; Neilan, Tomas G.; Mitchell, Richard; Moreno, Heitor; Kwong, Raymond; Jerosch‐Herold, Michael
Abstract : Background: Nearly 50% of patients with heart failure (HF) have preserved LV ejection fraction, with interstitial fibrosis and cardiomyocyte hypertrophy as early manifestations of pressure overload. However, methods to assess both tissue characteristics dynamically and noninvasively with therapy are lacking. We measured the effects of mineralocorticoid receptor blockade on tissue phenotypes in LV pressure overload using cardiac magnetic resonance (CMR). Methods and Results: Mice were randomized tol ‐nitro‐ω‐methyl ester (l ‐NAME, 3 mg/mL in water; n=22), orl ‐NAME with spironolactone (50 mg/kg/day in subcutaneous pellets; n=21). Myocardial extracellular volume (ECV; marker of diffuse interstitial fibrosis) and the intracellular lifetime of water (τic ; marker of cardiomyocyte hypertrophy) were determined by CMR T1 imaging at baseline and after 7 weeks of therapy alongside histological assessments. Administration ofl ‐NAME induced hypertensive heart disease in mice, with increases in mean arterial pressure, LV mass, ECV, and τic compared with placebo‐treated controls, while LV ejection fraction was preserved (>50%). In comparison, animals receiving both spironolactone andl ‐NAME ("l ‐NAME+S") showed less concentric remodeling, and a lower myocardial ECV and τic, indicating decreased interstitial fibrosis and cardiomyocyte hypertrophy (ECV: 0.43±0.09 forl ‐NAME versus 0.25±0.03 forl ‐NAME+S, P <0.001; τic : 0.42±0.11 forl ‐NAME groups versus 0.12±0.05 forl ‐NAME+S group). Mice treated with a combination ofl ‐NAME and spironolactone were similar to placebo‐treated controls at 7 weeks. Conclusions: Spironolactone attenuates interstitial fibrosis and cardiomyocyte hypertrophy in hypertensive heart disease. CMR can phenotype myocardial tissue remodeling in pressure‐overload, furthering our understanding of HF progression.